The Principal’s Strategy in Realizing a Vocational High School Center of Excellence in Indonesia - Bidandari, Aroum; Setyowati, Sri; Roesminingsih, Erny; Hariyati, Nunuk; Muavi, Makbul (International Journal of Social Learning (IJSL), 2024)
This research aims to analyze and describe the strategies carried out by school principals to realize the Vocational High School Centre of Excellence (SMK PK). This research is a multi-site case study with a qualitative approach. Deep interviews, observation, and documentation techniques are used in this research to collect the data, and two data analysis techniques are single and cross-case data analysis. The research results show that the strategies used by school principals in realizing Vocational High Schools Centre of Excellence (SMK PK) include the following: 1) Facilitative Strategy such as availability of good educational facilities and infrastructure; Guest teacher of the World Business and Industrial; and the equipment is updated to suit world trends Business and Industrial needed, 2) Educational Strategy (re-educative strategy)such as upskilling and reskilling for Vocational High School teachers and internship program for productive teacher, 3) Persuasive Strategy such as collaboration between school principals and companion Collage in persuading the business world and industrial world;  Head of Special Job Fair (BKK) in conducting negotiations in recruiting employees from vocational school graduates, 4) Strength Strategies such as school principal policies and MOU of school and the Business World and Industrial Word(DU/DI).